PENGEMBANGAN KURIKULUM PAI BERBASIS MULTIKULTURAL (Perspektif Psikologi Pembelajaran) - Achmad Yusuf (Universitas Yudharta Pasuruan, 2019)
The curriculum is like a house that must have a foundation in order to stand tall, not collapse and can provide comfort for those who live in it from diverse backgrounds, the foundation is the foundation of the curriculum as his home, in order to provide comfort and convenience for students to study and make products that are useful for themselves, religion, society and country. Learning theories that underlie curriculum development include the following: (a) Power Psychology, (b) State mental theory, (c) Psychology of Behaviorism, (d) Theory of Connectionsism, (e) Gestalt Psychology, (f) Constructivism Learning Theory, and (g) Jean Piaget's Cognitivism Development Theory.